2022
DOI: 10.3390/cancers14163970
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters: Potential Targets in Glioblastoma

Abstract: For decades, glioblastoma multiforme (GBM), a type of the most lethal brain tumor, has remained a formidable challenge in terms of its treatment. Recently, many novel discoveries have underlined the regulatory roles of neurotransmitters in the microenvironment both physiologically and pathologically. By targeting the receptors synaptically or non-synaptically, neurotransmitters activate multiple signaling pathways. Significantly, many ligands acting on neurotransmitter receptors have shown great potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 244 publications
0
6
0
Order By: Relevance
“…Dopamine receptors have been linked to multiple physiological and pathological functions [29,30]. More recently, studies have shown that dopamine receptors are important in glioma initiation and progression and therefore represent potential therapeutic targets [31][32][33]. Our team has previously shown that thioridazine, a DRD antagonist, inhibits late autophagy by impairing the fusion between autophagosomes and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine receptors have been linked to multiple physiological and pathological functions [29,30]. More recently, studies have shown that dopamine receptors are important in glioma initiation and progression and therefore represent potential therapeutic targets [31][32][33]. Our team has previously shown that thioridazine, a DRD antagonist, inhibits late autophagy by impairing the fusion between autophagosomes and lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that the decreased number of mRNA encoding GABAAR subunits and loss of GABAAR in GBM may indicate a relationship between the number of functional GABAAR and the severity of the disease [120][121][122]. In addition, GBM may counteract the attenuation of GABA on cell proliferation through a decrease in the expression of GABAAR [123,124].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies suggest GBM overexpresses 5HT 7 R; hence, this receptor has attracted much attention as a potential therapeutic and diagnostic target [27]. Our previous studies evaluated aryl piperazines such as 1-( 99m Tc(CO) 3 - [6], and 99m Tc(CO) 3 - [7] were also applied as SPECT imaging agents.…”
Section: Discussionmentioning
confidence: 99%